A Novel Study Based on Fuzzy p-Ideals of BCI-Algebras - G. Muhiuddin; Nabilah Abughazalah; A. Mahboob; M. E. Elnair; Abdullah G. Alotaibi (Journal of Function Spaces)
In this paper, we propose the concept of ∈,∈∨j∗,qj-fuzzy p-ideals in “BCI-algebras.” We show that “∈,∈∨q-fuzzy p-ideals” and “∈∨j∗,qj,∈∨j∗,qj-fuzzy p-ideals” are “∈,∈∨j∗,qj-fuzzy p-ideals.” However, the converse is not true, then presented examples. For a BCI-algebra Y^, it has been shown that every ∈,∈∨j∗,qj-fuzzy p-ideal of Y^ is an ∈,∈∨j∗,qj-fuzzy ideals of Y^but not conversely, and then, an example is given. Furthermore in Y^, a connection between ∈,∈∨j∗,qj-fuzzy p-ideals and p-ideals is established.